Security and Privacy in Social Networks - Altshuler, Yaniv; Elovici, Yuval; Cremers, Armin B.; Aharony, Nadav; Pentland, Alex.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
n/a
Introduction to Security and Privacy in Social Networks -- Interdisciplinary Impact Analysis of Privacy in Social Networks -- Recognizing Your Digital Friends -- Encryption for Peer-to-Peer Social Networks -- Crowdsourcing and Ethics -- The Effect of Social Status on Decision-Making and Prices in Financial Networks -- Stealing Reality: When Criminals Become Data Scientists (or Vice Versa) -- Applications of k-Anonymity and ℓ-Diversity in Publishing Online Social Networks -- Links Reconstruction Attack -- An Analysis of Anonymity in the Bitcoin System -- Privacy-Preserving Data Integration using Decoupled Data.
Keywords: Computer science; Computer Communication Networks; Data protection; Computer Science; Computer Communication Networks; Systems and Data Security; Information Systems Applications (incl. Internet).